PRODUKSI ENTROPI DAN PERTAUTAN OSILATOR PADA MODEL BRUSSELLATOR - Erna (NIM : 20598508), Maria
Abstract : The calculation of the entropy production in Brussellator (I) model with the reaction mechanism : (1) A - X, (2) B + X -> Y + D, (3) 2X + Y -, 3X, (4) X -4 E has been investigated. The analysis of the system stability was carried out by solving Jacobian matrix of the differential equations to obtain the roots of characteristic equation. These result were tested by numerical program. The entropy production formulation has been derived from fundamental equations of thermodynamic with an assumption that the system is homogen and isothermal. From this calculation it is clear that the entropy production of oscillating reaction always has positive value and is fluctuated versus time. The reaction steps which are reversible causes higher and constant entropy production. This research also studied oscillation forms due to two coupled oscillators, that is Brussellator (I) and another model with the reaction mechanism: (1) C -* Y, (2) Y + E -a Z + R, (3) 2Y + Z -> 3Y, (4) Y -, Q (II). Three forms of the oscillation were found. The first form is a damped oscillation, then change into an undamped one, the second is an undamped oscillation, and the third is a direct damped oscillation.